Pipe Flow and Rheology of Cationic Surfactant Solutions - Usui, Hiromoto; Saeki, Takashi; Ito, Takayasu; Sakai, Rieko (KAGAKU KOGAKU RONBUNSHU, 1996)
Drag reduction caused by the addition of a cationic surfactant (Ethoquad O/12) and rheological characteristics of the surfactant solutions were experimentally investigated. It was found that the addition of 200-500 ppm Ethoquad O/12 was enough to obtain an effective drag reduction. This amount of addition was much lower than the previous reports. Also, Ethoquad O/12 caused a significant drag reduction even at lower temperature range adequate for cooling system. Apparent viscosity of Ethoquad O/12 solutions was measured over a wide range of shear rate. Numerical analysis for laminer pipe flow with radial variation of apparent viscosity resulted in partially successful explanation of velocity profile of surfactant pipe flow.